Analysis of the Conditions of Access and Use of ICT and LKT in Remote Teaching and their Impact in the Linguistic Aspect in First-Year Students of the Bachelor’s Degree of English Teaching at Universidad Nacional, Coto Campus, in 2021 - Ávalos Rodríguez, Kiara Yeselin (2023)
This qualitative research paper explores the reality that freshman students lived in the Bachelor’s Degree in English Teaching at Universidad Nacional, Coto Campus, Brunca Region, during remote-teaching classes in 2021 with regard to accessibility, competence, and the importance of Information and Communication Technologies (ICTs) and Learning and Knowledge Technologies (LKTs). The information gathered shows that the competence in using these tools was very poor due to the students’ not having enough knowledge at the beginning of the semester. Also, the access to ICTs and LKTs was limited because of different factors that tend to happen in rural areas; therefore, it is necessary to work on trainings and the accessibility to these devices in the Brunca Region. However, the ICTs and LKTs were important to the learning and teaching process of these students because the results show that without these tools, the access to the lessons would not have been possible nor the development of the four linguistic skills of the English language.